Proposing the relationship between TQM and service quality in public university: A framework - Saberi, Nasarina; Romle, Abd Rahim; Abd Hamid, Siti Nur Illani (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Service quality considered as one of indicator to measure customer satisfaction in delivering of service.Hence, customer becomes an important actor due to they were expected satisfied during receiving the service. Whilst, the practices of total quality management (TQM) generally known through manufacturing industries rather than education sector.Indeed, the practices of TQM should be giving more attention in order to improve the quality standard in delivering the service.Hence, several dimensions of TQM were selected in order seeking better service performance and serve better quality of service. Thus, this article will proposed the relationship of TQM practices and service quality in public university.